Anesthesia for surgery related to craniosynostosis: a review. Part 2. Issue 1 (7th August 2012) - Hughes, Corinna; Thomas, Kate; Johnson, David; Das, Sumit
Summary The management of children with craniosynostosis is multidisciplinary and has evolved significantly over the past five decades. The treatment is primarily surgical. The anesthetic challenges continue to be the management of massive blood transfusion and prolonged anesthesia in small children, often further complicated by syndrome‐specific issues. This two‐part review aims to provide an overview of the anesthetic considerations for these children. The first part described the syndromes associated with craniosynostosis, the provision of services in the UK, surgical techniques, preoperative issues and induction and maintenance of anesthesia. This second part will explore hemorrhage control, the use of blood products, metabolic disturbance and postoperative issues.